2021
DOI: 10.1016/j.jiph.2021.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral diplopia and ptosis in a child with COVID-19 revealing third cranial nerve palsy

Abstract: We report the case of a 10-year-old boy with acute-onset diplopia and ptosis in the right eye. CR was positive for SARS-CoV-2. The patient was managed successfully with corticosteroids. We highlight the need for heightened suspicion of occult COVID-19 infection among children presenting with unusual III nerve palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Other cranial nerve palsies, with enhancement of the nerve at brain MRI, have been described ( 48 ). Particularly, cases of third cranial nerve palsy ( 79 81 ) revealed by unilateral diplopia and ptosis have been described with good outcomes after corticosteroid treatment.…”
Section: Clinical Consequences Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…Other cranial nerve palsies, with enhancement of the nerve at brain MRI, have been described ( 48 ). Particularly, cases of third cranial nerve palsy ( 79 81 ) revealed by unilateral diplopia and ptosis have been described with good outcomes after corticosteroid treatment.…”
Section: Clinical Consequences Of Sars-cov-2 Infectionmentioning
confidence: 99%
“… 8 Elenga et al and Prajwal et al showed inflammation of neurons in MRI of their cases, which could be caused by neuroinvasions via ACE-2 receptors. 11 12 ACE-2 receptors are considered as a key factor of neuro invasions, since ACE-2 is highly expressed in many neurons in human brain. 18–20 Gutiérrez-Ortiz et al reported a case with Miller-Fischer syndrome, an autoimmune disease that causes external ophthalmoplegia, ataxia and loss of tendon reflex, which is confirmed by a positive anti-GQ1b IgG antibody test.…”
Section: Discussionmentioning
confidence: 99%
“…Oculomotor nerve palsies caused by inflammation usually present themselves during MRI imaging with findings confined to the oculomotor nerve and without further brain or orbital ones, as seen in said patient. This case led to the heightened suspicion of SARS-CoV-2 infection among children with unusual third nerve palsy [ 68 ].…”
Section: Adnexa Of the Eyementioning
confidence: 99%